2017
DOI: 10.23937/2572-4053.1510016
|View full text |Cite
|
Sign up to set email alerts
|

Valeriana Officinalis and Melissa Officinalis Extracts Normalize Brain Levels of GABA and Glutamate Altered by Chronic Stress

Abstract: Despite being traditionally used herbals to treat mild anxiety and sleep disorders, Valeriana officinalis and Melissa officinalis mechanism of action is not fully understood. While the pattern of mood modulation of both herbals suggests the involvement of the Gamma-Aminobutyric Acid (GABA) ergic system, other changes in the neurotransmitters pathways can provide an explanation for the clinical effects. The aim of this study was to examine the combined mechanism of action of the two extracts in order to explain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“… 44 Extracts and phytochemicals of Melissa officinalis L., Lamiaceae, and Valeriana officinalis L., Caprifoliaceae, showed inhibitory activity against this enzyme. 45 , 46 Inhibition of GABA uptake is involved mainly with transport mechanisms, resulting in increased extracellular GABA levels, 47 which was also verified for the extract of Passiflora incarnata L., Passifloraceae. 48 …”
Section: Discussionmentioning
confidence: 73%
“… 44 Extracts and phytochemicals of Melissa officinalis L., Lamiaceae, and Valeriana officinalis L., Caprifoliaceae, showed inhibitory activity against this enzyme. 45 , 46 Inhibition of GABA uptake is involved mainly with transport mechanisms, resulting in increased extracellular GABA levels, 47 which was also verified for the extract of Passiflora incarnata L., Passifloraceae. 48 …”
Section: Discussionmentioning
confidence: 73%
“…The GABAergic neurons inhibit HPA activity by reducing the secretion of adrenocorticotropic hormone [41,42]. However, under stressful condition there is depletion of GABA receptor binding in the CNS [43,44] which leads to the activation of the HPA axis. Studies have shown that extracts and active compounds of ashwagandha have GABA-like activity and also increase the production of GABA in brain [45][46][47].…”
Section: Discussionmentioning
confidence: 99%